Public Perceptions of Whistleblowing. (2nd January 2016) - Heumann, Milton; Friedes, Al; Redlawsk, David; Cassak, Lance; Kesari, Aniket
Abstract : This article reports the results of a two-pronged exploration of public perceptions of whistleblowing, the first using a statewide public opinion poll, and the second, a laboratory experiment in which a multistage scenario determined respondents' support for an employee's protest actions and their classification of the employee as a whistleblower. One substantial finding is that self-interest taints the purity of the employee's motivation making it less likely for respondents to classify the employee as a whistleblower. The employee's gender, the type of action protested, and whether the employee worked in the public or private sector were randomly manipulated, with no significant differences in respondents' support or classification of whistleblowing. Implications for future research are discussed.